2016
DOI: 10.1371/journal.pone.0147375
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin-1 Mediated Cardioprotection Involves XIAP and CD40-Ligand Recovery: Role of EPAC2 and ERK1/2

Abstract: AimsUrocortin-1 (Ucn-1) is an endogenous peptide that protects heart from ischemia and reperfusion (I/R) injuries. Ucn-1 is known to prevent cardiac cell death, but its role in the transcription of specific genes related to survival signaling pathway has not been fully defined. The aim of this study was to investigate the molecular signaling implicated in the improvement of cardiac myocytes survival induced by Ucn-1.Methods and ResultsUcn-1 administration before ischemia and at the onset of reperfusion, in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…However, a recent study demonstrated that both Epac isoforms are present within mitochondria isolated from adult rat myocytes (Wang et al, 2016). Current findings using rat hearts have implied that the cardioprotective effect induced by urocortin‐1 is mediated by activation of Epac2 (Calderon‐Sanchez et al, 2016) and that Epac2 inhibition promotes cardiac arrhythmias (Yang et al, 2016). Nonetheless, in the absence of direct evidence, a role for the Epac1 isoform cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study demonstrated that both Epac isoforms are present within mitochondria isolated from adult rat myocytes (Wang et al, 2016). Current findings using rat hearts have implied that the cardioprotective effect induced by urocortin‐1 is mediated by activation of Epac2 (Calderon‐Sanchez et al, 2016) and that Epac2 inhibition promotes cardiac arrhythmias (Yang et al, 2016). Nonetheless, in the absence of direct evidence, a role for the Epac1 isoform cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…"Clearly, the development of the first antagonists with (subtype) selectivity for EPAC represents another research milestone to ascribe biologic responses to EPAC" (915). Indeed, these selective EPAC2 inhibitors are becoming effective tools in probing isoform-specific EPAC functions (18,47,130,175,226,250,302,411,463,565,682,743,841,896,961,1114).…”
Section: B Epac Specific Antagonistsmentioning
confidence: 99%
“…38 Interestingly, it is reported that Urocortin-1 prevented the heart from ischemia and reperfusion injury by increasing cell survival and stimulating the apoptosis-related genes CD40lg, XIAP, and BAD. 39 Recently, studies have shown that the interaction of miRNAs and their target genes can affect the progression of human diseases. For example, miR-146a prohibits against myocardial ischaemia reperfusion injury via targeting Med1.…”
Section: Discussionmentioning
confidence: 99%